Teaching Buddhism in New Zealand Universities - Huang, Li Ting (Auckland University of Technology, 2009)
This thesis is an investigation into the university-level teaching of Buddhism in New Zealand, which has developed as part of the international spread of education about Buddhism for both Buddhists and non-Buddhists. The study was based on Interpretivism and accordingly sought to understand and interpret university teachers’ perceptions and experiences about their teaching of Buddhism; as they engage with the students' learning in this field. Semi-structured in-depth interviews were employed as the primary research method. All seven university teachers who teach Buddhism in New Zealand were invited to be the participants. Six university teachers participated in this research-study. Five of them were academic teachers, respectively teaching at Religious Studies of Massey, Victoria and Otago. Another one was a New Zealand-born Zen teacher who had been teaching a Zen meditation workshop at Auckland University of Technology for several years, and taught two Buddhism-related courses at the University of Auckland. These participants were chosen according to the information provided on official websites of New Zealand universities. The findings from the study showed that the university-level teaching of Buddhism in New Zealand, though growing, had been limited by the number of teachers and students. As fewer students were primarily interested in Buddhism, outward funding support appeared to be a very important factor for its future development. In terms of teachers’ role, objective-outsider remained the main position for scholars and scholar-practitioners in teaching Buddhism in university classroom. In addition to the pursuit of knowledge, there were also alternative educational opportunities, such as Zen workshop, for university staffs and students to learn Buddhism, outside university classroom. This thesis is significant in that it provided a bibliography and a set of data for the university-level teaching of Buddhism in the West, particularly New Zealand It established a space for future educational research into for the university-level teaching of Buddhism in the West, as part of the field of 'Buddhism and Education.’ In future studies, the limited approaches to teaching Buddhism in universities could be investigated on the basis of the literatures and findings of this study.
Keywords: Buddhist studies; University; Interpretivist approach; Semi-structured interview; New Zealand; Teaching religion